Repurposing Copper(II)/THPTA as A Bioorthogonal Catalyst for Thiazolidine Bond Cleavage - Chengyun Ma; Guoqing Liu; Juan Yin; Jianan Sun; Disheng Luo; Dechun Yang; Shuo Pang; Wei Hou; Xinya Hemu; Bangce Ye; Xiaobao Bi (Advanced Science)
Abstract Metal‐mediated chemical transformations are promising approaches to manipulate and regulate proteins in fundamental biological research and therapeutic development. Nevertheless, unlike bond‐forming reactions, the exploration of selective bond cleavage reactions catalyzed by metals that are fully compatible with proteins and living systems remains relatively limited. Here, it is reported that Copper(II)/tris(3‐hydroxypropyltriazolylmethyl)amine (THPTA), commonly used in copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) reaction, can be repurposed as a new bioorthogonal catalyst for thiazolidine (Thz) bond cleavage. This process liberates an α‐oxo‐aldehyde group under physiological conditions, without requiring additional additives. To showcase the utility of this method, this simple catalyst system is coupled with genetic code expansion technology to achieve on‐demand activation of genetically encoded Thz‐caged α‐oxo‐aldehydes, enabling further functionalization of proteins. For the first time, this cell‐compatible Thz uncaging reaction allows for the site‐specific installation of α‐oxo‐aldehydes at the internal positions of proteins in phage and bacterial surface display systems, expanding the chemical space of proteins. Overall, this study expands the toolkit of bioorthogonal catalysts and paves the way for metal‐promoted chemical reactions in living systems, potentially benefiting various applications in the future.